Effects of napier and cattail grasses on open channel flow characteristics - Abood, Manal M. (2005)
Laboratory study has been conducted to analyze the effects of two types of vegetations namely Napier grass and Cattail grass on the characteristics of flow in an open channel. The main objectives of this study are to determine the effects of vegetations on Manning’s roughness coefficient and velocity distribution, and to develop relationships between the characteristics of vegetation (density, degree of submergence and distribution) with the properties of flow (Manning roughness coefficient, velocity and Reynolds number). The resistance properties for each of vegetation were examined in the flume which is rectangular in cross section and has dimensions of 12m length, 0.32m width and 0.32m height. The results show that the presence of vegetations increases the values of Manning’s roughness coefficient, n, and affected significantly the vertical velocity profiles. The effects depend on factors such as flow depth, degree of submergence, density and arrangement of plant. The Manning’s roughness coefficient, n, for flows with Napier grass increased with the increased in flow depth for both submerged and unsubmerged situations, and this increments varied from 0.017 to 0.065 with flow depth for high vegetation density (100 veg/m2) and from 0.0058 to 0.0427 for low vegetation density (20 veg/m2). In the presence of Cattail grass, the effects were reversed. The increased in flow depth leads to reduction in the roughness coefficient, and this decrements varied from 0.031 to 0.022 for the high density and from 0.024 to 0.0157 for the low density. This may be due to the physical characteristics of the cattail, which has no branching stems and leaves. Manning’s n in the case of low density (20 veg/m2) of Napier grass decreased with the increase of Reynolds number, Re for both submerged and unsubmerged vegetations. However, for higher density (100 veg/m2), this phenomenon only occurred for submerged vegetation. In the case of unsubmerged vegetation the n values increased with the increased of Re. For cattail, the n values decreased with Re for all densities of vegetation. The dependence of n on density of vegetation was found to be represented by a linear relationship (R2=.093-0.96) for both submerged and unsubmerged vegetations. The results indicate a tendency for n to increase with increasing values of density for the same value of flow depth. Napier grass increased the Manning’s, n with the increased of density by 35%, while the Cattail grass increased the value of n with the increased of density by 25%. Increment in Manning’s, n with the density of vegetation is not only with the flow depth but also with the different types of vegetation. The manning roughness coefficient, n was also found to be affected by the vegetation arrangement. The results show that the arrangement where the vegetations were at both sides of the channel gave the highest values of n followed by the vegetations at the channel center and then the vegetations were randomly distributed. The n value increased almost linearly with the depth of flow in three types of arrangements. The effects of vegetations in the vertical velocity distribution of flow were examined, the results showed that the present of vegetation change the shape of velocity distribution and reduced the velocity by 61.5% inside the canopy and 36% above the canopy.